EFFECT OF JACKFRUIT (Artocarpus heterophyllus Lamk.) PEEL EXTRACTS ON LIPID PROFILE IN RATS FED A HIGH FAT DIET - Aulia, Andina Putri; Oktiarto, Wahyu; Sulistyaningsih, Nur; -, Sampurna (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2019)
Hyperlipidemia is an increase in one or more of lipid including total cholesterol, triglycerides, LDL or decreased HDL. A High lipid level in the blood is a strong marker of the risk factors for cardiovascular diseases. One of the most commonly used anti-hyperlipidemic drugs is statin groups. The purpose of this study was to determine the effect of giving jackfruit peel extract on the lipid profile in rat fed a high-fat diet. Experimental study of post-test only control group design. Male white wistar rats were divided into 4 groups: negative control, positive control, treatment groups (jackfruit extract 500mg / 200gBW / day and 750mg / 200gBW /day) . The treatment was given for 14 days, and the levels of total cholesterol, triglycerides, LDL and HDL were evaluated. The data were tested for normality and homogeneity with Saphiro-Wilk Test and Leuvene’s Test respectively followed by One Way Anova and Post Hoc LSD tests if the data were normally distributed and homogeneous. Otherwise, the data were tested with Kruskal Walis followed by Mann Whitney. There were significant differences in cholesterol, triglyceride, LDL and HDL parameters (p <0.05). Dose 750mg/200gBW/day of Jackfruit peel extract was more effective for improving lipid profile clinically than dose 500mg /200gBw/ day but less effective compared to simvastatin. The administration of 500mg/200gBW /day jackfruit extract and 750mg/200gBW/ day decreased lipid profile in rat fed a High Fat Diet .